Assessment of Oropharyngeal and Laryngeal Cancer Treatment Delay in a Private and Safety Net Hospital System. (10th April 2018) - Perlow, Haley K.; Ramey, Stephen J.; Silver, Ben; Kwon, Deukwoo; Chinea, Felix M.; Samuels, Stuart E.; Samuels, Michael A.; Elsayyad, Nagy; Yechieli, Raphael
Abstract : Objective: To examine the impact of treatment setting and demographic factors on oropharyngeal and laryngeal cancer time to treatment initiation (TTI). Study Design: Retrospective case series. Setting: Safety net hospital and adjacent private academic hospital. Subjects and Methods: Demographic, staging, and treatment details were retrospectively collected for 239 patients treated from January 1, 2014, to June 30, 2016. TTI was defined as days between diagnostic biopsy and initiation of curative treatment (defined as first day of radiotherapy [RT], surgery, or chemotherapy). Results: On multivariable analysis, safety net hospital treatment (vs private academic hospital treatment), initial diagnosis at outside hospital, and oropharyngeal cancer (vs laryngeal cancer) were all associated with increased TTI. Surgical treatment, severe comorbidity, and both N1 and N2 status were associated with decreased TTI. Conclusion: Safety net hospital treatment was associated with increased TTI. No differences in TTI were found when language spoken and socioeconomic status were examined in the overall cohort.